Synthesis and Characterization of Some New Derivatives Starting from (4, 4'-diaminophenoxy) Ethane Containing Diazonium Groups - Iftikhar Ahmed Hussein (Journal of Global Pharma Technology, 2019)
The diazonium salts are highly reactive compounds. They are used as intermediate in different reactions. The diazonium salt [C2] was synthesized and reacted upon with (Acetyl acetone, ethyl acetoacetate, salicyladehyde) to produce [C3-C5].Then reacted [C3, C4] with hydrazine hydrate 80% due to [C6,C7] . Then reacted [C5] with (Methyldopa and Atenolol) as drugs obtained [C8, C9].The prepared derivatives were identified by infrared spectra, 1HNMR, and physical properties.Keywords: Azo compounds, Heterocyclic rings, Schiff bases.